2000
DOI: 10.1046/j.1365-2796.2000.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ketoacids on plasma creatinine assays in diabetic ketoacidosis

Abstract: Acetoacetate caused severe interference of the alkaline picrate (Jaffé) assay, which might influence therapeutic decisions at the start of diabetic ketoacidosis. Enzymatic assays lack this interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In the setting of DKA, the elevated creatinine may be due to volume depletion caused by polyuria, a false positive result caused by the increased level of acetoacetate in the body, or diabetic nephropathy. 20 Our cohort has higher rates of short-term mortality compared with other studies 13 ; there are several possible explanations for this. First, patients in Scotland who are admitted to hospital with DKA and who require critical care admission are most likely to be managed in High Dependency Units.…”
Section: Discussionmentioning
confidence: 60%
“…In the setting of DKA, the elevated creatinine may be due to volume depletion caused by polyuria, a false positive result caused by the increased level of acetoacetate in the body, or diabetic nephropathy. 20 Our cohort has higher rates of short-term mortality compared with other studies 13 ; there are several possible explanations for this. First, patients in Scotland who are admitted to hospital with DKA and who require critical care admission are most likely to be managed in High Dependency Units.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, the creatinine level that we used to calculate eGFR via the Schwartz formula was measured using the Jaffe method. In children with metabolic ketoacidosis, the presence of acetoacetate may have resulted in falsely elevated serum creatinine levels if measured using the Jaffe method [38]. However, the Jaffe method is the most widely used approach to measure serum creatinine in our country and the only assay available that measures serum creatinine level at our institution.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In this study creatinine assessments were carried out with the enzymatic method. Kemperman showed that the enzymatic plasma creatinine assay is superior to estimations obtained with alkaline picrate analysis [27]. The accuracy of the formulae in this study could be influenced by the way of measuring creatinine in blood.…”
Section: Discussionmentioning
confidence: 71%